Changes of Serum CEA Level after Resection of Colorectal Carcinoma - Kabir, Md Jahangir; Bhuiyan, AKM Minhaj Uddin; Rahman, Md Mizanur (Journal of Surgical Sciences, 2019)
Introduction :Carcinoembryonic antigen is the most commonly used tumour associatedantigen in the management of patients with colorectal carcinoma. The test appearsuseful to determine prognosis and to monitor patients with colorectal carcinoma for earlyrecurrence, persistent elevation of CEA for a month after operation suggests thepresence of occult metastatic disease. Objective: The study was done to compare pre and postoperative CEA level in colorectalcarcinoma patient and to analyze the relationship of CEA and different Dukes stage inpre operative period of colorectal carcinoma patients. Methods: This cross-sectional and cohort study was performed to look at the change inCEA level among 97 colorectal carcinoma patients in pre and post operative state in thedepartment of surgical oncology, NICRH from January 2010 to June 2012. Results :Statistically significant changes was found in pre and postoperative CEA levelin colorectal carcinoma patient (p <.001). Preoperative CEA level was raised in Dukes8(40%) and Dukes C(54%). Conclusion :Postoperative CEA level was significantly reduced after resection of colorectalcarcinoma and neck neoplasm. Journal of Surgical Sciences (2016) Vol. 20 (1) : 3-6